Comparison between plethysmography and body fat equations in elite taekwondo athletes - Quintero, A. M.; Fonseca, S.; Chagnaud, C. A.; De la Rosa, A. (Ido Movement for Culture. Journal of Martial Arts Anthropology, 2022)
Background. In taekwondo, body composition and body fat percentage (BF%) are decisive factors in the result of combat between elite athletes. In recent years, air displacement plethysmography (ADP) has appeared as a reference method to evaluate BF%, while skinfold-based equations can be used in those cases in which people are unable to access such equipment. Problem and Aim: To determine the degree of agreement between the BF% estimated by the ADP method and by different skin- fold-based equations in male taekwondo athletes. Methods. 12 elite Brazilian male athletes (19.5± 3.8 years old) were evaluated using the International Society for the Advancement of Kinanthropometry (ISAK) protocol. BF% was estimated using 9 skinfold-based equations whose results were compared with those of the ADP method. Results. The mean of the BF% measured using the reference method was 8.9 ± 5.4. Agreement between skinfold based equations and ADP methods was examined by the Bland-Altman method. The narrowest limits of agreement relative to the reference were for the Katch & McArdle skinfold-based equation (-5.5, 5.9) containing 95% (11/12) of the score difference. The mean difference (bias) of the measurements between ADP and the anthropometric methods was (0.18±2.9). Conclusions. These results suggest that the Katch & McArdle equation, applying body density from the Brozek et al equation. [1963], could be considered the most appropriate method to determine BF%, as its results are closest to those established by the ADP method. This equation presents good repeatability and concordance, small percentage error, and ease of use in the body fat evaluation of taekwondo athletes.